The Muqaddimah an introduction to history - Ibn Khaldun, 1332-1406 (Bollingen series / Princeton, 1989)
The Muqaddimah, often translated as "Introduction" or "Prolegomenon," is the most important Islamic history of the premodern world. Written by the great fourteenth-century Arab scholar Ibn Khaldûn (d. 1406), this monumental work laid down the foundations of several fields of knowledge, including philosophy of history, sociology, ethnography, and economics. The first complete English translation, by the eminent Islamicist and interpreter of Arabic literature Franz Rosenthal, was published in three volumes in 1958 as part of the Bollingen Series and received immediate acclaim in America and abroad. A one-volume abridged version of Rosenthal's masterful translation was first published in 1969. This new edition of the abridged version, with the addition of a key section of Rosenthal's own introduction to the three-volume edition, and with a new introduction by Bruce B. Lawrence, will reintroduce this seminal work to twenty-first-century students and scholars of Islam and of medieval and ancient history.